An Arsenal of Arguments: Arabic Philosophy at the Service of Christian Polemics in Ramon Martí’s Pugio fidei - Giletti, A (Warburg Institute, 2014)
This article addresses the question of audience for Ramon Marti's Pugio fidei, Book I (c. 1278). Books II and III are a polemic against Judaism and addressed to Jews, while Book I is attacks the errors of philosophy against religion, with no stated audience. Book I contains many quotations from Arabic philosophical sources, translated into Latin for the first time by Marti. To address the question of audience, the article examines the structure of Pugio fidei, I (which is deliberately based on al-Ghazali's Deliveror from Error) and its content (much of it from Aquinas's Summa contra gentiles). The article shows the harmony of Aquinas and al-Ghazali on the relationship between faith and reason as evidenced in Pugio fidei. It also shows it is unlikely that Latin scholastics were the intended audience (because of the philosophical issues treated and the reliance on al-Ghazali), but that Marti's target was possibly a Muslim audience, with the aim of implementing the method of converting Muslims to Christianity by means of rational argumentation as proposed by Aquinas in Summa contra gentiles.